Defensive Discourse in Writing about Music - Fred Everett Maus (Zeitschrift der Gesellschaft für Musiktheorie)
A simple conception of musical experience positions music as an active force, listeners as passive. A defensive resistance to passivity sometimes leads music theory and analysis, and other discourses about music, to divert attention from listening, understood as feminized, while working to establish powerful, active roles for composers, music, and theorists. The essay explores the effects of the active/passive opposition in writing by Eduard Hanslick, Hector Berlioz, John Rahn, Allen Forte, and Edward T. Cone. These analyses summarize fuller treatments by the author in previous essays, here drawn together to show the shared concerns of these writers. The essay concludes by offering ways to complicate or evade simple dualities of active and passive.